Повышение надёжности трансмиссии колёсного бронетранспортёра БТР-4Е за счёт введения в гидросистему автономного контура смазки и охлаждения раздаточной коробки - Слюсаренко, Ю. А.; Початовский, С. В.; Галушка, Ю. В. (НТУ "ХПИ", 2012)
Предложен метод повышения надёжности трансмиссии колёсного бронетранспортёра БТР-4Е и машин на его базе, за счёт введения в гидросистему автономного контура смазки раздаточной коробки.

The method increase reliability transmission of a wheel armored personnel carrier BTR-4Е and machines on its base, due to introduction in hydrosystem of an independent contour of greasing distributing box is offered.
Increase reliability transmission of the wheel armored personnel carrier BTR-4E due to introduction in hydrosystem of the independent contour of greasing and cooling distributing box
Keywords: техника бронетанковая; момент крутящий; колесо ведущее; жидкость рабочая; насос нагнетающий; редуктор; клапан смазки